Value-based planning for capability evolution - Shibui, Takashi (Cranfield University, 2023)
Systems such as military equipment can be viewed as capability components constituting capability systems alongside others (e.g., interoperating systems, personnel, etc.). Capability systems are developed to perform the tasks of their acquirer organisation and realise the capabilities identified in the organisation’s capability planning. Also, they are continuously engineered for the capabilities’ evolution. In this time-dependent context, individual systems need to sustain their value to the acquirer. Their design ought to be better aligned with the overarching capability development. Two challenges were identified regarding this goal: 1. Evaluation of design alternatives based on their contribution to the organisational capability, corresponding to the top-level organisational task. It should account for the organisation’s priorities concerning different capability areas. 2. Exploration of design evolution alternatives considering the long planning horizons, expecting future changes and uncertainties regarding the capability needs and the system’s context (e.g., adversaries, environment, etc.). To address them, a novel framework was developed. It incorporates: • Value-based evaluation of design alternatives. It is founded on a value metric formally defined to represent the contribution to the organisational capability. Two methods were developed to estimate the “value”: The first method determines task importance reflecting the acquirer’s needs. The second method estimates the achieved capability levels by identifying the trade-off relationships of factors regarding the system design and context. • Scenario planning method. It allows to model different futures using codified change trajectories of needs and contextual factors. By calculating value trajectories of the evolving system alternatives for the scenarios, what-if analysis to aid decisions is made possible. • A consistent domain ontology underpinning the framework. It defines and relates concepts from relevant industrial domains. The proposed framework and methods were tested and evaluated with representative test cases. Evaluation by industrial practitioners was also performed. The results showed the framework’s usefulness and relevance to real-world practices.
Riaz, Atif - Associate Supervisor
Keywords: Capability-Based Planning; Capability Systems Engineering; Value-Centric Design Methodologies; Decision Analysis; Structural Equation Modelling; future needs